Evaluasi Kinerja Heat Exchanger 05 (HE-05) Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi Cepu (PPSDM MIGAS Cepu) - Dwita Cahaya Pratiwi (Swara Patra, 2022)
The heat exchanger is one of the important units for processing petroleum which acts as a heat exchanger between fluids through solid media. The Cepu Oil and Gas Human Resources Development Center (PPSDM Migas Cepu) itself has five heat exchangers with details of three (HE-01 and HE-02) arranged horizontally and two vertically (HE-03, HE-04, and HE-05). The five HEs have shell and tube types and the same function, namely as a preheater by utilizing heat from the distillation unit before the crude oil enters the furnace. In addition to these uses, the preheater on the HE can also reduce utility costs in the form of using a heater in the production process. This study aims to observe the performance of HE-05 in PPSDM Migas Cepu and determine whether the condition of HE-05 is still considered optimal for operation. Observations were made using a quantitative approach method through the calculation of heat transfer efficiency. The results of the calculation of the efficiency of HE-05 from the residual heat capacity of 85,753 liters/day and 319,853 liters of crude oil/day are 82.52%. This efficiency indicates that heat transfer in heat exchanger 05 is still optimal for operation because it is still above 80%.